Numerical Simulation of Steel Target Penetration by Shaped Charge Distended Jet with a High-Polymer Liner - Yi, J.Y.; Wang, Z.J.; Yin, J.P.; Chang, B.H. (Проблемы прочности, 2017)
This study investigates the characteristics of shaped charge jet formed with a high-polymer (PTFE) liner, as well as its penetration capabilities, by theoretical, experimental, and numerical methods. This work presents a viscoplastic model and equation of compressible fluid to describe the jet cohesive condition. It also shows that the high-polymer jet is inevitably distended. Two types of liner materials were studied: a high-polymer PTFE liner and a pure copper one. The corresponding numerical simulations of the two jet formations are presented. The pulse X-ray photographic technology was employed to observe the distended jet of the PTFE liner and the particulate jet of the copper one. The simulation and jet radiography results show that the two types of jet behavior with particulate and radial dispersion are ductile and related to the liner material. The distended jet formation result from the liner material was crushed at the high-pressure region because a sudden pressure jump induces the radial velocity rise, which results in lateral expansion. As compared with a typical copper penetration performance, the polymer distended jet had a larger aperture and lower penetration depth. Due to polymer liner lower density, this jet will have limited penetration as compared to that of a copper liner. The simulated results strongly agree with the experimental ones. The polymer material can be modified to obtain much better performance, which will greatly enhance the penetration capacity of polymer jets.